Ultrasonic coupling material composition, ultrasonic coupling material film, and ultrasonic inspection method

By combining polysilicon oxygen adhesive with silicone oil without crosslinking points, a soft and water-resistant ultrasonic coupling material film is formed, solving the problems of unstable and residual ultrasonic signal transmission in the prior art, and achieving efficient and safe ultrasonic inspection.

CN119307100APending Publication Date: 2025-01-14SHIN ETSU CHEMICAL CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202410926780.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-12
Filing Date
2024-07-11
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Existing ultrasonic coupling materials are prone to failure due to moisture after long-term use, and cannot stably transmit ultrasonic signals. Residues may be left after peeling, affecting skin health.

Method used

An ultrasonic coupling material composed of polysilicon oxygen adhesive and silicone oil without crosslinking points is used to form a film through addition hardening reaction to ensure the softness and elasticity of the film while avoiding residue.

Benefits of technology

Ultrasonic examination is achieved in which ultrasonic transmission is not reduced under water wet or dry conditions. There is no skin residue after peeling, and it has excellent biocompatibility, reducing irritation to the skin.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307100A_ABST
    Figure CN119307100A_ABST
Patent Text Reader

Abstract

The invention relates to an ultrasonic coupling material composition, an ultrasonic coupling material film, and an ultrasonic inspection method. The present invention addresses the problem of providing an ultrasonic coupling material film which is lightweight and can be produced at low cost, while having high ultrasonic transmission and sensitivity and excellent biocompatibility by embedding unevenness in the skin. [Solution] An ultrasonic coupling material composition containing (A) a silicone adhesive and (B) a silicone oil having no cross-linking point, the component (A) being a mixture or a condensation reaction product of a diorganopolysiloxane (a) having a viscosity at 25 DEG C of 100,000 mPa * s or more and a resin composition (b) containing an MQ resin and an organic solvent, and the component (B) being a mixture or a condensation reaction product of the diorganopolysiloxane (a) having a viscosity at 25 DEG C of 100,000 mPa * s or more and the resin composition (b) containing an MQ resin and an organic solvent. The component (B) is a silicone oil having no crosslinking point and having a dynamic viscosity in the range of 10-100,000 mm2 / s at 25 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an ultrasonic coupling material composition, an ultrasonic coupling material film, and an ultrasonic inspection method. Background Art

[0002] In recent years, with the popularization of IoT (Internet of Things), the development of wearable devices has also progressed. Clocks and glasses that can connect to the Internet are representative examples. In addition, in the medical field and sports field, wearable devices that can monitor the body's condition at any time have become necessary and are expected to grow in the future.

[0003] For example, a watch-type wearable device equipped with an optical sensor, an electrostatic capacitance sensor, an ultrasonic sensor, a pressure sensor, etc. has been proposed (Patent Document 1).

[0004] Wearable devices capable of ultrasonic diagnosis have also been studied, which can visualize the conditions of organs and blood vessels in the body and measure pulse and blood pressure at any time (Patent Document 2).

[0005] The ultrasonic diagnostic instrument can make the ultrasonic probe close to the skin, and use the ultrasonic transmitter to make the ultrasonic waves emitted from the probe surface bounce in the body, and detect the information in the body through the probe receiver. During ultrasonic measurement, if the measured surface has unevenness and the surface of the ultrasonic probe cannot cover the unevenness of the measured surface and there is an air layer, the ultrasonic waves emitted from the surface of the ultrasonic probe will be reflected by the air layer and cannot reach the body. Therefore, during ultrasonic diagnosis, a water-soluble gel-based coupling material is inserted between the surface of the ultrasonic probe and the skin (Patent Document 3). Patent Document 4 exemplifies many water-soluble coupling materials.

[0006] If the ultrasonic wave is to be measured only once, a water-soluble gel-based coupling material is applied to the skin, and the ultrasonic probe is brought into close contact therewith to perform the measurement, and the gel on the skin surface after the measurement is wiped off with a cloth or paper containing water, or washed with water. However, if the ultrasonic probe is attached for a long time for measurement, the water-soluble gel will dissolve if sweating occurs during exercise, or if the coupling material is showered or bathed while the probe is attached, and the ultrasonic signal cannot be received without the coupling material. Therefore, there is a problem that the gel-based coupling material cannot be used for long-term installation purposes.

[0007] Therefore, water-insoluble coupling materials have been proposed, for example, paraffin-based materials (Patent Document 5) and silicone gel-based materials (Patent Document 6).

[0008] If it is a water-soluble gel coupling, it can be easily removed after the measurement as mentioned above, but when paraffin wax or silicone remains on the skin, it is necessary to wipe it with paper or cloth soaked in paraffin oil, etc., which is not easy to remove. Silicone gel is a low-crosslinked silicone rubber. When silicone oil is added to it, the silicone oil may remain in the skin, and it is necessary to remove the residual silicone oil after peeling.

[0009] Therefore, for long-term installation purposes, non-water-soluble coupling materials for ultrasonic measurement are desired, and there is a need to develop coupling materials that leave no residue on the skin after the coupling materials are peeled off from the skin after ultrasonic measurement, and that have high ultrasonic penetration and sensitivity due to covering the unevenness of the skin.

[0010] Prior art literature

[0011] Patent Literature

[0012] [Patent Document 1] Japanese Patent Application Publication No. 2021-093127

[0013] [Patent Document 2] International Publication No. 2020 / 049934

[0014] [Patent Document 3] Japanese Patent Application Laid-Open No. 46-000146

[0015] [Patent Document 4] Japanese Patent Publication No. 2005-532871

[0016] [Patent Document 5] Japanese Patent Application Laid-Open No. 63-019135

[0017] [Patent Document 6] U.S. Patent No. 9211106 Summary of the invention

[0018] [Problems to be solved by the invention]

[0019] The present invention is made to solve the above-mentioned problems, and its purpose is to provide an ultrasonic coupling material composition, ultrasonic coupling material film, and ultrasonic inspection method that can cover the unevenness of the skin and has high ultrasonic transmissibility and sensitivity and excellent biocompatibility, is lightweight and can be manufactured at low cost, and even if it is wetted or dried, the ultrasonic transmissibility will not be greatly reduced, is soft and has excellent elasticity, and will not leave any residue on the skin after peeling, and will not cause roughness of the skin.

[0020] [Methods to solve the problem]

[0021] In order to solve the above problems, the present invention provides an ultrasonic coupling material composition, comprising (A) a polysilicone adhesive and (B) a silicone oil without crosslinking points, characterized in that:

[0022] The aforementioned polysiloxane adhesive (A) is a mixture or condensation reaction product of a diorganopolysiloxane (a) and a resin composition (b), wherein the viscosity of the diorganopolysiloxane (a) at 25° C. is 100,000 mPa·s or more, and the resin composition (b) contains a 1 3 SiO 1 / 2 and SiO 2 Unit resin and organic solvent; R 1 A hydrogen atom or a substituted or unsubstituted monovalent hydrocarbon group having 1 to 10 carbon atoms;

[0023] The aforementioned (B) silicone oil without crosslinking points has a dynamic viscosity of 10 to 100,000 mm at 25°C. 2 / s range.

[0024] If such an ultrasonic coupling material composition is used, it will embed the unevenness of the skin and have high ultrasonic transmissibility, sensitivity and excellent biocompatibility. It is lightweight and can manufacture the ultrasonic coupling material membrane at low cost. Even if it is wetted or dried by water, the ultrasonic transmissibility will not be greatly reduced. It is soft and has excellent elasticity. After peeling, no residue will remain on the skin and it will not cause skin roughness.

[0025] In the present invention, the diorganopolysiloxane (a) is preferably a diorganopolysiloxane (a1) having an alkenyl group.

[0026] When such a diorgano group polysiloxane (a) is contained, the alkenyl groups serve as crosslinking points, thereby forming an ideal ultrasonic coupling material film.

[0027] In this case, it is preferred to further contain an organohydrogenpolysiloxane having a SiH group as the component (C), and it is more preferred to further contain a platinum-based catalyst.

[0028] The diorganosiloxane (a1) having an alkenyl group and the organohydrogenpolysiloxane (C) having a plurality of SiH groups can be cross-linked by an addition reaction using a platinum-based catalyst.

[0029] In this case, the value obtained by dividing the number of moles of SiH groups in the component (C) by the number of moles of alkenyl groups in the component (A) is preferably in the range of 0.5 to 20.

[0030] With such a composition, an ideal ultrasonic coupling material film can be obtained by utilizing an addition hardening reaction.

[0031] In the present invention, the component (B) is preferably a linear or branched diorganopolysiloxane having no alkenyl group or SiH group.

[0032] Such a component (B) is preferred in the present invention.

[0033] The value obtained by dividing the mass of the component (B) by the solid content of the components (a) and (b) and the total mass of the components (B) and (C) is preferably in the range of 0.2 to 0.8.

[0034] By setting the mass of the component (B) within such a range, an ideal ultrasonic coupling material film can be obtained.

[0035] It is preferred that 0.1 to 10 parts by mass of dry silica is further contained based on 100 parts by mass of the total of the solid content of the components (a) and (b) and the components (B) and (C).

[0036] The composition of the present invention contains dry silica, which improves the strength of the obtained ultrasonic coupling material film. When peeled off from the release liner, the film is not easily broken and can be easily attached to the skin or the ultrasonic probe.

[0037] Furthermore, the present invention provides an ultrasonic coupling material film composed of a cured product of the ultrasonic coupling material composition.

[0038] The ultrasonic coupling material membrane of the present invention covers the unevenness of the skin and has high ultrasonic transmission and sensitivity and excellent biocompatibility. It is lightweight and its ultrasonic transmission will not be significantly reduced even if it is wetted or dried. It is soft and has excellent elasticity. After peeling off, no residue will remain on the skin and it will not cause skin roughness.

[0039] At this time, the thickness of the ultrasonic coupling material film is preferably in the range of 10 to 10000 μm.

[0040] When the film thickness is within the above range, the ultrasonic wave transmission and sensitivity are excellent, the film is lightweight and has excellent softness and elasticity, no residue remains on the skin after peeling, and the film will not cause skin roughness, and the effect is higher.

[0041] Furthermore, the present invention provides a single ultrasonic coupling material film characterized in that the ultrasonic coupling material film is a self-supporting film that is separated from a support and independent.

[0042] The ultrasonic coupling material film of the present invention can also be made into a self-supporting film (individual film) for use, which is easy to handle during ultrasonic inspection.

[0043] The present invention also provides a laminated structure comprising a support and the ultrasonic coupling material film directly in contact with the support.

[0044] The ultrasonic coupling material film of the present invention can be used as a self-supporting film or as a structure in which the ultrasonic coupling material film is laminated on a support (laminated structure), which is easy to handle during ultrasonic inspection.

[0045] In addition, the present invention provides a method for forming a laminated structure characterized by coating the above-mentioned ultrasonic coupling material composition on a peeling liner film, heating and hardening it to form an ultrasonic coupling material film, then peeling off the above-mentioned peeling liner film from the above-mentioned ultrasonic coupling material film and attaching the ultrasonic coupling material film to another support body, so that the ultrasonic probe is attached to the surface opposite to the surface contacting the above-mentioned other support body to form a laminated structure.

[0046] Furthermore, the ultrasonic coupling material composition may be coated on a peeling lining film, heated and hardened to form an ultrasonic coupling material film, and then, the peeling lining film is peeled off from the ultrasonic coupling material film and the ultrasonic coupling material film is attached to an ultrasonic probe to form a laminated structure. Alternatively, the ultrasonic coupling material composition may be coated on an ultrasonic probe, heated and hardened to form an ultrasonic coupling material film to form a laminated structure.

[0047] Since the ultrasonic coupling material composition can be coated on a release liner film and an ultrasonic probe and then heated and hardened for use, the desired state can be selected as described above to form a laminated structure during ultrasonic inspection.

[0048] Furthermore, the present invention provides a method for performing ultrasonic examination by attaching the ultrasonic probe to the skin with the surface having the ultrasonic coupling material film formed thereon, which is characterized by being a method for forming the above-mentioned laminated structure, but excluding methods for performing surgery, treatment or diagnosis on humans.

[0049] The ultrasonic coupling material film formed using the ultrasonic coupling material composition of the present invention has excellent ultrasonic penetrability and sensitivity as well as excellent water resistance, and there is no residue on the skin after measurement, which can reduce the burden on the subject. Therefore, it is very useful in various ultrasonic examinations such as long-term installation purposes.

[0050] [Effects of the Invention]

[0051] As described above, if it is the ultrasonic coupling material composition of the present invention, it will embed the unevenness of the skin and have high ultrasonic transmissibility and sensitivity and excellent biocompatibility. It is lightweight and can be manufactured at low cost. Even if it is wet or dry, the ultrasonic transmissibility will not be greatly reduced. It is soft and has excellent elasticity. After peeling, no residue will remain on the skin and it will not cause skin roughness. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] [ Figure 1 ] is a schematic cross-sectional view showing an example of the coupling material membrane of the present invention.

[0053] [ Figure 2 ] is a schematic cross-sectional view showing another example of the coupling material membrane of the present invention.

[0054] [ Figure 3 ] is a schematic cross-sectional view showing an example of the use of the coupling material film of the present invention being attached to the skin.

[0055] [ Figure 4 ] A schematic cross-sectional view showing an example of the use of the coupling material film of the present invention attached to an ultrasonic probe.

[0056] [ Figure 5 ] is a schematic cross-sectional view showing an example of the use of the coupling material membrane of the present invention attached between an ultrasonic probe and skin.

[0057] [ Figure 6 ] is a schematic cross-sectional view showing an example of performing ultrasonic diagnosis in a state where the coupling material membrane of the present invention is attached between an ultrasonic probe and skin.

[0058] [ Figure 7 ] is a schematic cross-sectional view showing an example of performing ultrasonic diagnosis in a state where a known coupling material film is attached between an ultrasonic probe and the skin.

[0059] [ Figure 8 ] is a photograph of the coupling material film of the present invention attached to a wrist.

[0060] [ Fig. 9 ] is a photograph of the water-soluble gel lubricant of Comparative Example 5 dispensed on the wrist.

[0061] [ Fig.10 ] is a photograph of a handheld ultrasonic diagnostic instrument (device) viewed from the ultrasonic probe side.

[0062] [ Fig.11 ] is to Figure 1 A photograph of an ultrasonic coupling material film in a cross-sectional state, attached to an ultrasonic probe while peeling off the release liner.

[0063] [ Fig.12 ] is a photograph showing an ultrasonic measuring device placed on a coupling material film and performing ultrasonic diagnosis.

[0064] [ Fig.13 ] is a photograph of an ultrasonic image when an ultrasonic signal is obtained well.

[0065] [ Fig.14 ] is a photograph of an ultrasonic image when an ultrasonic signal cannot be obtained smoothly. DETAILED DESCRIPTION

[0066] As described above, it is required to develop a coupling material composition that is non-water-soluble and has excellent skin unevenness, sound wave penetration, and biocompatibility, is lightweight and can be manufactured at low cost, is soft and has elasticity and strength, can contact the skin for a long time and can stably collect ultrasonic signals regardless of whether it is wet or dry due to bathing, sweating, etc., the coupling laminated membrane, and its ultrasonic measurement method.

[0067] As a coupling material that is non-water-soluble and has excellent sonic permeability and biocompatibility, silicone materials can be cited. Patent Document 6 discloses a coupling material using silicone gel. Silicone gel is a cross-linked, very soft silicone rubber with ultra-low density. However, in order to embed the micron-sized micro-convexities of soft skin, softness alone is not enough.

[0068] In order to make the silicone gel softer, a method of adding non-crosslinked silicone oil or hydrocarbon-based mineral oil as described in Japanese Patent Publication No. 2015-028178 can be cited. The addition of non-crosslinked silicone oil will improve the embedding properties of the skin's unevenness, and when used as an ultrasonic coupling material, it will improve the sensitivity of ultrasonic measurement. However, when a large amount of non-crosslinked silicone oil is added, it will seep out, and when the coupling material film is peeled off from the skin after the ultrasonic measurement is completed, silicone oil residue will be generated on the skin. If there is silicone oil residue, in order to remove it, it is necessary to wipe the skin with a towel or cotton wool soaked in mineral oil, which is time-consuming and less ideal.

[0069] Therefore, the inventors have repeatedly studied the above issues and have designed a silicone adhesive instead of a silicone gel to prevent leakage even when a large amount of non-crosslinked silicone oil is added. The silicone adhesive is a crosslinked silicone with R 1 3 SiO 1 / 2 and SiO 2 The reaction product or mixture of MQ resin with units is to prevent the non-crosslinked silicone oil from leaking out. The inventors have found that if the ultrasonic coupling material composition contains such a polysilicone adhesive and silicone oil without crosslinking points, the above-mentioned problems can be solved, and the present invention is completed.

[0070] That is, the present invention is an ultrasonic coupling material composition, comprising (A) a polysilicone adhesive and (B) a silicone oil without crosslinking points, characterized in that:

[0071] The aforementioned polysiloxane adhesive (A) is a mixture or condensation reaction product of a diorganopolysiloxane (a) and a resin composition (b), wherein the viscosity of the diorganopolysiloxane (a) at 25° C. is 100,000 mPa·s or more, and the resin composition (b) contains a 1 3 SiO 1 / 2and SiO 2 Unit resin and organic solvent; R 1 A hydrogen atom or a substituted or unsubstituted monovalent hydrocarbon group having 1 to 10 carbon atoms;

[0072] The aforementioned (B) silicone oil without crosslinking points has a dynamic viscosity of 10 to 100,000 mm at 25°C. 2 / s range.

[0073] Thus, the present invention relates to a coupling material membrane inserted between the skin and an ultrasonic diagnostic instrument for measuring pulse and blood pressure, which contacts the skin of a living body and visualizes the conditions of organs and blood vessels in the body, a coupling material composition for providing the coupling material membrane, and a method for manufacturing the coupling material membrane.

[0074] Hereinafter, the present invention will be described in detail, but the present invention is not limited thereto.

[0075] <Ultrasonic Coupling Material Composition>

[0076] The ultrasonic coupling material composition of the present invention contains a polysilicone adhesive, silicone oil without cross-linking points, and an organic solvent.

[0077] In the ultrasonic coupling material composition of the present invention, the polysilicone adhesive (A) is a mixture of components (a) and (b) or a mixture of a condensation reaction product and an organic solvent, component (a) is a diorgano group polysiloxane, and component (b) is a polysiloxane having R 1 3 SiO 1 / 2 and SiO 2 The unit resin and organic solvent preferably have a dynamic viscosity of 10 to 100,000 mm at 25°C. 2 / s range of silicone oil (B) component without crosslinking points, organohydrogen polysiloxane (C component), and a platinum catalyst. 1 It is a hydrogen atom or a substituted or unsubstituted monovalent hydrocarbon group having 1 to 10 carbon atoms.

[0078] Hereinafter, each component will be described in further detail.

[0079] [(A)Component]

[0080] (A) The silicone adhesive is a diorganopolysiloxane (a) having a viscosity of 100,000 mPa·s or more at 25°C and a 1 3 SiO 1 / 2 and SiO 2 A mixture or condensation product of a resin composition (b) containing a resin having a unit and an organic solvent; R 1 It is a hydrogen atom or a substituted or unsubstituted monovalent hydrocarbon group having 1 to 10 carbon atoms.

[0081] ((a) ingredient)

[0082] The component (a) blended in the ultrasonic coupling material composition of the present invention is a diorganopolysiloxane having a viscosity of 100,000 mPa·s or more at 25°C. If it is such, it is not particularly limited, and it is preferably a diorganopolysiloxane (a1) having an alkenyl group. The diorganopolysiloxane having an alkenyl group can use the component (A1) described in Japanese Patent Application Laid-Open No. 2015-193803, and the viscosity at 25°C is 100,000 mPa·s or more.

[0083] Examples of the alkenyl group include vinyl, allyl, hexenyl, octenyl, acryloylpropyl, acryloylmethyl, methacryloylpropyl, and vinyloxypropyl groups, and vinyl groups are particularly preferably used.

[0084] The group other than the alkenyl group is a substituted or unsubstituted monovalent hydrocarbon group having 1 to 10 carbon atoms. Specifically, alkyl groups such as methyl, ethyl, propyl and butyl, cycloalkyl groups such as cyclohexyl, aryl groups such as phenyl and tolyl, and groups in which a part or all of the hydrogen atoms bonded to the carbon atoms of these groups are substituted with other groups such as halogen, amino, hydroxyl or cyano; for example, 3-aminopropyl, 3,3,3-trifluoropropyl, 3-hydroxypropyl and 3-cyanopropyl are mentioned. Methyl and phenyl are particularly preferred.

[0085] In addition, component (a) may also contain a component (A2) corresponding to component (A2) described in Japanese Patent Publication No. 2015-193803, and a diorgano group polysiloxane (a2) having a viscosity of 100,000 mPa·s or more at 25°C and having no alkenyl group. The polymers of A1 and A2 are terminated with hydroxyl groups or alkoxy groups, and may also be bonded by condensing them with the silanol groups in the MQ resin of component (b). In this case, component (a) and component (b) are not independent components, but become an integrated component. The condensation reaction can be carried out by using an acid catalyst or a basic catalyst and heating.

[0086] The polysiloxanes a1 and a2 may be linear or branched.

[0087] Adhesive silicone resins include those of the addition reaction hardening type and free radical crosslinking reaction hardening type. In the addition hardening type, alkenyl groups and SiH groups are crosslinked by addition reaction, and the free radical hardening type will crosslink not only when alkenyl groups are present, but also even if alkenyl groups are not present. At this time, crosslinking with the silicone oil (B) component that does not have a crosslinking group can also be caused. Therefore, there is a possibility that the fluidity of the silicone oil is reduced, the embedding performance of the skin is reduced, and the sensitivity as an ultrasonic coupling material is reduced. Therefore, the addition hardening type is more ideal than the free radical crosslinking type.

[0088] In addition, a modified siloxane having a group selected from an amino group, an oxirane group, an oxetane group, a polyether group, a hydroxyl group, a carboxyl group, a mercapto group, a methacrylic group, an acrylic group, a phenol group, a silanol group, a carboxylic anhydride group, an aryl group, an aralkyl group, an amide group, an ester group, and a lactone ring may be added as the component (a). The modified siloxane may be one in which one end, both ends, or a side chain of the siloxane is modified.

[0089] Reducing the amount of octamethylcyclotetrasiloxane and decamethylcyclopentasiloxane in component (a) is effective in reducing skin irritation. The method for reducing the amount is described in Japanese Patent Application Laid-Open No. 2015-193803.

[0090] Components (a1) and (a2) may be either in the form of oil or in the form of raw rubber. When in the form of raw rubber, if the viscosity is as high as more than 500,000 mPa·s, the viscosity when dissolved in toluene at a concentration of 30% by mass (30% by mass solution viscosity) is preferably 100,000 mPa·s or less. In addition, the 30% by mass solution viscosity is preferably 1,000 to 60,000 mPa·s. If the 30% by mass solution viscosity exceeds 100,000 mPa·s, the composition will become excessively viscous and stirring during manufacture will become difficult. In addition, in the present invention, the viscosity (absolute viscosity) is a value measured at 25°C using a rotational viscometer.

[0091] [(b) Component]

[0092] (b) contains R 1 3 SiO 1 / 2 and SiO 2 Unit resin (R 1 A resin composition comprising a hydrogen atom or a substituted or unsubstituted monovalent hydrocarbon group having 1 to 10 carbon atoms and an organic solvent.

[0093] The resin in component (b) is a resin having R 1 3 SiO 1 / 2 Unit (M unit) and SiO 2 The so-called MQ resin has a unit (Q unit) and is in a form dissolved in an organic solvent. 1 It is a hydrogen atom or a substituted or unsubstituted monovalent hydrocarbon group having 1 to 10 carbon atoms. The organic solvent for dissolving the MQ resin may be appropriately selected from the organic solvents described below.

[0094] R 1It is a hydrogen atom or a substituted or unsubstituted monovalent hydrocarbon group having 1 to 10 carbon atoms, for example, alkyl groups such as methyl, ethyl, propyl and butyl, aryl groups such as cycloalkyl, phenyl, and alkenyl groups such as vinyl, allyl and hexenyl. In addition, some or all of the hydrogen atoms bonded to the carbon atoms of these groups are substituted by other groups such as halogen, amino, hydroxyl or cyano, for example, 3-aminopropyl, 3,3,3-trifluoropropyl, 3-hydroxypropyl and 3-cyanopropyl.

[0095] Ideal R 1 3 SiO 1 / 2 Unit / SiO 2 The number ratio of the units is 0.6 to 1.7. When the number ratio is at least the lower limit, the adhesive force and the tackiness will not be reduced, and when it is at most the upper limit, the adhesive force and the holding power will be good.

[0096] The component (b) may also have an OH group, and the OH group content is preferably 0.01 to 4.0% by mass of the total mass of the component (B). When the OH group content is above the lower limit, the cohesive force of the adhesive is high, and when it is below the upper limit, the viscosity of the adhesive will not be reduced. Usually, the MQ resin of the component (b) has a silanol group, which can form a chemical bond by condensing with the hydroxyl or alkoxy terminal of the diorganopolysiloxane in the component (a).

[0097] Two or more components (b) may be used in combination. 1 SiO 3 / 2 Unit (T unit) and / or R 1 2 SiO unit (D unit).

[0098] The presence of component (b) provides adhesiveness and prevents component (B) from seeping out and component (B) from remaining on the skin after the coupling material is peeled off.

[0099] The solid content ratio of the components (a) and (b) (the ratio of the solid content other than the organic solvent in the component (A)) is 20 to 100 parts by mass of the component (a), and the component (b) can be 1 to 20 parts by mass per 120 parts by mass of the total component (A).

[0100] [(B) ingredient]

[0101] Component (B) is a silicone oil having no crosslinking point (non-crosslinking type) and having a dynamic viscosity of 10 to 100,000 mm at 25°C. 2 / s, preferably 50~50000mm 2 / s. In the present invention, the dynamic viscosity is a value measured at 25°C using an Oswald viscometer.

[0102] Component (B) is a fluid oil when used alone. By adding component (B), when the ultrasonic coupling material film is attached to the skin, the fine concave-convex parts of the skin can be buried and the penetration of ultrasonic waves can be improved.

[0103] The non-crosslinked silicone oil of the component (B) is not particularly limited as long as its dynamic viscosity at 25°C is within the above range, and is preferably a linear or branched diorganopolysiloxane having no alkenyl group or SiH group. Such a component (B) has good affinity with the silicone adhesive (A), and even if a large amount of non-crosslinked silicone oil is added, there is no bleeding, so oil bleeding can be prevented.

[0104] The value obtained by dividing the mass of component (B) by the solid content of components (a) and (b), the total mass of components (B) and (C) (the total mass of the solid content of components (A) to (C)) is preferably in the range of 0.2 to 0.8 (0.20 to 0.80), more preferably in the range of 0.3 to 0.78.

[0105] [(C) ingredient]

[0106] The component (C) is an organic group hydrogen polysiloxane having a SiH group as the component (C). When the polysiloxane adhesive has an alkenyl group, the alkenyl group and the SiH group will be cross-linked (addition hardening) by an addition reaction (hydrosilylation reaction), and the component (C) at this time can function as a cross-linking agent. If the component (C) is an organic group hydrogen polysiloxane having a SiH group, there is no particular restriction, for example, the component (C) described in Japanese Patent Publication No. 2015-193803 can be used (having more than 2 SiH groups in the molecule, preferably 3 or more).

[0107] The viscosity of component (C) at 25°C is preferably 1 to 1,000 mPa·s, and more preferably 2 to 500 mPa·s. Component (C) may also be a mixture of two or more. It may be a straight chain, branched, or cyclic structure. The number of SiH groups in one molecule of the organic group hydrogen polysiloxane is preferably 2 or more. More preferably, it is 3 or more. When the composition is an addition-curing type, such a component (C) is preferably used. When the MQ resin of component (b) has SiH groups, component (C) is not necessary.

[0108] The diorganosiloxane (a1) having alkenyl groups and the organohydrogenpolysiloxane (C) having multiple SiH groups can be crosslinked by an addition reaction using a platinum catalyst. The ratio of the number of moles of SiH groups divided by the number of moles of alkenyl groups is preferably in the range of 0.5 to 20, more preferably in the range of 1 to 15.

[0109] Examples of platinum-based catalysts include chloroplatinic acid, alcohol solutions of chloroplatinic acid, reaction products of chloroplatinic acid and alcohols, reaction products of chloroplatinic acid and olefin compounds, reaction products of chloroplatinic acid and vinyl-containing siloxanes, platinum-olefin complexes, platinum-vinyl-containing siloxane complexes and other platinum-based catalysts, rhodium complexes, ruthenium complexes and other platinum group metal catalysts, etc. In addition, those obtained by dissolving or dispersing these catalysts in alcohol-based, hydrocarbon-based, or siloxane-based solvents may also be used.

[0110] The amount of platinum catalyst added is preferably 5 to 2,000 ppm, preferably 10 to 500 ppm (calculated as metal mass), relative to 100 parts by mass of the resin solution (ultrasonic coupling material composition) comprising (A), (B), (C) and an organic solvent.

[0111] When an addition-curing silicone resin is used, an addition reaction control agent may be added as a quencher to prevent the platinum catalyst from acting in a solution or in a low temperature environment before heat curing after the coating is formed. Specific examples thereof include 3-methyl-1-butyn-3-ol, 3-methyl-1-pentyn-3-ol, 3,5-dimethyl-1-hexyn-3-ol, 1-ethynylcyclohexanol, 3-methyl-3-trimethylsilyloxy-1-butyn, 3-methyl-3-trimethylsilyloxy-1-pentyn, 3,5-dimethyl-3-trimethylsilyloxy-1-hexyn, 1-ethynyl-1-trimethylsilyloxycyclohexane, bis(2,2-dimethyl-3-butynyloxy)dimethylsilane, 1,3,5,7-tetramethyl-1,3,5,7-tetravinylcyclotetrasiloxane, and 1,1,3,3-tetramethyl-1,3-divinyldisiloxane.

[0112] The amount of the addition reaction control agent added is preferably 0 to 10 parts by mass, particularly preferably 0.05 to 3 parts by mass, based on 100 parts by mass of the resin solution.

[0113] [Silicon dioxide particles]

[0114] Dry silica particles may also be added to the composition of the present invention. By adding dry silica, the strength of the ultrasonic coupling material film is improved, the film is not easily broken when peeled off from the release liner, and it is easy to stick to the skin and ultrasonic probe. The specific surface area of ​​dry silica is 50 to 500 m 2 / g range, preferably 100~400m 2 / g. The specific surface area can be measured by the BET method. Silica in which the silanol on the surface of the silica is replaced by trimethylsilyl, dimethylsilyl, or dimethylpolysiloxy has high dispersibility and is more ideal. Dry silica can also be commercially available, for example, AEROSIL RX200 (manufactured by NIPPON AEROSIL) can be used.

[0115] The dry silica is preferably added in an amount of 0.1 to 10 parts by mass based on 100 parts by mass of the total of the solid contents of the components (a) and (b), the components (B) and (C) (the total solid contents of the components (A) to (C)).

[0116] [Organic solvents]

[0117] Furthermore, in addition to the organic solvent contained in the above-mentioned component (b), the composition of the present invention may further contain the same or other organic solvents. By adjusting the type and amount of the organic solvent contained in the composition of the present invention, the workability can be improved.

[0118] The organic solvent is not particularly limited, and examples thereof include the following. Specifically, examples thereof include toluene, xylene, isopropylbenzene, 1,2,3-trimethylbenzene, 1,2,4-trimethylbenzene, 1,3,5-trimethylbenzene, styrene, α-methylstyrene, butylbenzene, sec-butylbenzene, isobutylbenzene, isopropyltoluene, diethylbenzene, 2-ethyl-p-xylene, 2-propyltoluene, 3-propyltoluene, 4-propyltoluene, 1,2,3,5-tetramethyltoluene, 1,2,4,5-tetramethyltoluene, tetralin, 4-phenyl-1-butene, tert-pentylbenzene, pentylbenzene, 2-tert-butyltoluene, 3-tert-butyltoluene, 4-tert-butyltoluene, 5-isopropyl-m-xylene, 3-methylethylbenzene, tert-butyl-3-ethylbenzene, 4-tert-butyl-o-xylene, 5-tert-butyl-m-xylene, tert-butyl-p-xylene, 1,2 - Aromatic hydrocarbon solvents such as diisopropylbenzene, 1,3-diisopropylbenzene, 1,4-diisopropylbenzene, dipropylbenzene, pentamethylbenzene, hexamethylbenzene, hexylbenzene, 1,3,5-triethylbenzene, etc.; n-heptane, isoheptane, 3-methylhexane, 2,3-dimethylpentane, 3-ethylpentane, 1,6-heptadiene, 5-methyl-1-hexyne, norbornane, norbornene, dicyclopentadiene, 1-methyl-1,4-cyclohexadiene, 1-heptyne, 2-heptyne, cycloheptane, cycloheptene, 1,3-dimethylcyclopentane, ethylcyclopentane, methylcyclohexane, 1-methyl-1-cyclohexene, 3-methyl-1-cyclohexene, methylenecyclohexane, 4-methyl-1-cyclohexene, 2-methyl-1-hexene, 2-methyl-2-hexene, 1 -heptene, 2-heptene, 3-heptene, n-octane, 2,2-dimethylhexane, 2,3-dimethylhexane, 2,4-dimethylhexane, 2,5-dimethylhexane, 3,3-dimethylhexane, 3,4-dimethylhexane, 3-ethyl-2-methylpentane, 3-ethyl-3-methylpentane, 2-methylheptane, 3-methylheptane, 4-methylheptane, 2,2,3-trimethylpentane, 2,2,4-trimethylpentane, cyclooctane, cyclooctene, 1,2-dimethylcyclohexane, 1,3-dimethylcyclohexane, 1,4-dimethylcyclohexane, ethylcyclohexane, vinylcyclohexane, isopropylcyclopentane, 2,2-dimethyl-3-hexene, 2,4-dimethyl-1-hexene, 2,5-dimethyl-1- Hexene, 2,5-dimethyl-2-hexene, 3,3-dimethyl-1-hexene, 3,4-dimethyl-1-hexene, 4,4-dimethyl-1-hexene, 2-ethyl-1-hexene, 2-methyl-1-heptene, 1-octene, 2-octene, 3-octene, 4-octene, 1,7-octadiene, 1-octyne, 2-octyne, 3-octyne, 4-octyne, n-nonane, 2,3-dimethylheptane, 2,4-dimethylheptane, 2,5-dimethylheptane, 3,3-dimethylheptane, 3,4-dimethylheptane, 3,5-dimethylheptane, 4-ethylheptane, 2-methyloctane, 3-methyloctane, 4-methyloctane, 2,2,4,4-tetramethylpentane, 2,2,4-trimethylhexane, 2,2,5-Trimethylhexane, 2,2-dimethyl-3-heptene, 2,3-dimethyl-3-heptene, 2,4-dimethyl-1-heptene, 2,6-dimethyl-1-heptene, 2,6-dimethyl-3-heptene, 3,5-dimethyl-3-heptene, 2,4,4-trimethyl-1-hexene, 3,5,5-trimethyl-1-hexene, 1-ethyl-2-methylcyclohexane, 1-ethyl-3-methylcyclohexane, 1-ethyl-4-methylcyclohexane, propylcyclohexane, isopropylcyclohexane, 1,1,3-trimethylcyclohexane cyclohexane, 1,1,4-trimethylcyclohexane, 1,2,3-trimethylcyclohexane, 1,2,4-trimethylcyclohexane, 1,3,5-trimethylcyclohexane, allylcyclohexane, octahydroindane (hydrindane), 1,8-nonadiene, 1-nonyne, 2-nonyne, 3-nonyne, 4-nonyne, 1-nonene, 2-nonene, 3-nonene, 4-nonene, n-decane, 3,3-dimethyloctane, 3,5-dimethyloctane, 4,4-dimethyloctane, 3-ethyl-3-methylheptane, 2-methyl 1-Decahydronaphthalene, 1-Decyne, 2-Decyne, 3-Decyne, 4-Decyne, 5-Decyne, 1,5,9-Decatriene, 2,6-Dimethyl-2,4,6-Octadi ... myrcene), 1,2,3,4,5-pentamethylcyclopentadiene, α-phellandrene, pinene, terpinene, tetrahydrodicyclopentadiene, 5,6-dihydrodicyclopentadiene, dicyclopentadiene, 1,4-decadiyne, 1,5-decadiyne, 1,9-decadiyne, 2,8-decadiyne, 4,6-decadiyne, n-undecane, pentylcyclohexane, 1-undecene, 1,10-undecadiene, 1-undecyne, 3-undecyne, 5-undecyne, tricyclo[6.2.1.0, 2,7 ] undec-4-ene, n-dodecane, n-tridecane, n-pentadecane, n-hexadecane, 2-methylundecane, 3-methylundecane, 4-methylundecane, 5-methylundecane, 2,2,4,6,6-pentamethylheptane, 1,3-dimethyladamantane, 1-ethyladamantane, 1,5,9-cyclododecatriene, 1,2,4-trivinylcyclohexane, aliphatic hydrocarbon solvents such as isoalkanes. They may also be any mixture.

[0119] The hydrocarbon solvent is an aliphatic solvent and does not include an aromatic solvent. More specifically, it is preferably mainly straight-chain alkanes, isoalkanes, cycloalkanes (naphthenes) or a mixture thereof. Straight-chain alkanes and isoalkanes have less odor than cycloalkanes, so if straight-chain alkanes, isoalkanes, or a mixture of the two are used, the odor can be reduced and the burden on the environment and human body can be reduced, so it is more ideal. The straight-chain alkanes, isoalkanes, or a mixture of the two here refer to solvents with highly purified straight-chain alkanes, isoalkanes, or a mixture of the two as the main component. Usually, in these highly purified solvents, there are still trace amounts of cycloalkanes and aromatics mixed in the ppm level to a maximum of about 0.5% or less (mass basis). However, the influence of these trace components on the odor is so small that it can be roughly ignored. Therefore, the straight-chain alkanes, isoalkanes or mixtures thereof herein refer to those which do not substantially contain cycloalkanes and aromatics in an amount equal to or greater than the trace impurity level as described above.

[0120] Alternatively, commercially available organic solvents may be used, such as ISOPAR M (ISOPAR TM M), "ISOPAR G" (ISOPAR TM G) (ExxonMobil Corporation), "IP Solvent 2028" (Idemitsu Kosan), branched paraffin solvent mixtures, especially isoparaffinic hydrocarbons, or "Exxsol D110" (Exxsol TM (ExxonMobil Corporation), "AF Solvent No. 4" (ENEOS) and other cycloparaffinic hydrocarbons. ISOPAR (registered trademark) series of isoparaffinic solvents are preferred. They have the characteristics of low reactivity and stability, low toxicity and high safety, and little odor.

[0121] The amount of the organic solvent added is preferably in the range of 10 to 50,000 parts by mass based on 100 parts by mass of the total of the resins (a) and (b) (solid content of the (b) resin composition).

[0122] [Other additives]

[0123] In the ultrasonic coupling material composition of the present invention, in addition to the above-mentioned dry silica, wet silica, aluminum oxide particles, titanium oxide particles, zirconium oxide particles, and pigments can also be mixed. By adding wet silica particles, aluminum oxide particles, titanium oxide particles, and zirconium oxide particles, the strength will be improved. Pigments will be added during coloring. Aluminum oxide particles, titanium oxide particles, and zirconium oxide particles can be used ideally in either dry or wet form, and those whose surfaces are treated with a water-repellent silicon-based agent have excellent dispersibility. The shapes of wet silica, aluminum oxide particles, titanium oxide particles, and zirconium oxide particles are spherical, elliptical, irregular, hollow, and porous.

[0124] <Ultrasonic coupling material film>

[0125] The ultrasonic coupling material film silicon of the present invention is composed of a hardened material of the above-mentioned ultrasonic coupling material composition.

[0126] In the present invention, the ultrasonic coupling material composition is used to form an ultrasonic coupling material film on a support such as a peeling liner film, and the film is inserted between the skin and the ultrasonic probe to implement ultrasonic transmission between the skin and the ultrasonic probe.

[0127] Hereinafter, the ultrasonic coupling material (film) of the present invention will be described in detail with reference to the drawings, but the present invention is not limited thereto.

[0128] Figure 1 This is a schematic cross-sectional view showing an example of the ultrasonic coupling material film of the present invention. Figure 1 The ultrasonic coupling material 1 is shown in a form formed on a release liner (support) 2.

[0129] The substrate of the release liner can be selected from paper, plastic film made of plastic, glass, metal, cloth, etc. Paper can be listed as: high-quality paper, coated paper, art paper, glass paper, polyethylene laminated paper, kraft paper, Japanese paper, synthetic paper, etc. Plastic film can be listed as: polyethylene film, polypropylene film, polyester film, polyimide film, polyamide film, polyvinyl chloride film, polyvinylidene chloride film, polyvinyl alcohol film, polycarbonate film, polytetrafluoroethylene film, polystyrene film, ethylene-vinyl acetate copolymer film, ethylene-vinyl alcohol copolymer film, triacetyl cellulose film, polyetheretherketone film, polyphenylene sulfide film, etc. There is no special restriction on the thickness and type of glass, and chemically strengthened treatments can also be used. In addition, glass fiber can also be used, and glass fiber can be used as a monomer or as a composite with other resins. Cloth can be listed as: natural fiber cloth, synthetic fiber cloth and artificial leather, etc., and metal examples include: aluminum foil, copper foil, gold foil, silver foil, nickel foil, etc. Among them, paper and plastic film are preferred, and polyester film is particularly preferred.

[0130] The release force can also be reduced by coating the fluorine-based release agent described in Japanese Patent Application Laid-Open Nos. 2020-100763 and 2020-100764 on the substrate of the release liner.

[0131] <Method for producing ultrasonic coupling material film>

[0132] The method for producing the ultrasonic coupling material film of the present invention is not particularly limited, and a production example will be described below with reference to the drawings.

[0133] First, the ultrasonic coupling material composition of the present invention is coated on a support (substrate) such as a release liner. The method for coating the ultrasonic coupling material composition on a substrate such as a release liner is not particularly limited, and suitable methods include: dip coating, spray coating, spin coating, rod coating, teasing coating, slit coating, roller coating, flow coating, blade coating, screen printing, flexographic printing, gravure printing, inkjet printing, etc.

[0134] Then, the ultrasonic coupling material composition coated on the support (substrate) is hardened.

[0135] The method for curing the ultrasonic coupling material composition is not particularly limited. For example, the applied film is preferably cured by either heat or light, or both.

[0136] The temperature during heating is not particularly limited, but is preferably about 50 to 250° C. Heating may be by electric heating such as warm air or a hot plate, or by heating such as infrared or microwave irradiation.

[0137] When heating and irradiation with light, infrared or microwave are combined, heating and irradiation with light, infrared or microwave may be performed simultaneously, heating may be performed after irradiation with light, infrared or microwave, or irradiation with light, infrared or microwave may be performed after heating. In addition, air drying may be performed after coating in order to evaporate the solvent before heating.

[0138] The thickness of the ultrasonic coupling material film after heat curing is preferably 10 to 10000 μm, more preferably 10 to 4000 μm, and even more preferably 20 to 3000 μm. In the numerical ranges of the aforementioned film thicknesses, the upper limit can be arbitrarily set to 5000 μm, 2000 μm, 500 μm, or 400 μm, and the lower limit can be arbitrarily set to 30 μm, 50 μm, 100 μm, or 120 μm, or any combination thereof can be used.

[0139] Instead of coating the ultrasonic coupling material composition on the release liner, it may be coated on the ultrasonic probe.

[0140] like Figure 2As shown, the ultrasonic coupling material film 1 can be structured so that the upper and lower parts are sandwiched by the release liner 2. This makes it possible to easily transport the ultrasonic coupling material film having adhesiveness.

[0141] <How to use the ultrasonic coupling material film>

[0142] like Figure 3 As shown, Figure 2 The single-sided release liner 2 is peeled off and the ultrasonic coupling material film 1 is attached to the skin 3.

[0143] like Figure 4 As shown, the ultrasonic coupling material film 1 can also be attached to the ultrasonic probe 4.

[0144] Ultrasound diagnosis, such as Figure 5 As shown, the structure of the ultrasonic coupling material film 1 is sandwiched between the skin 3 and the ultrasonic probe 4.

[0145] In ultrasound diagnosis, the ultrasound waves emitted from the ultrasound probe are transmitted to the skin through the ultrasound coupling material membrane. Figure 6 and 7 The frequency of ultrasonic waves is generally a sound wave with a frequency of 3 MHz or more used in ultrasonic diagnosis.

[0146] Figure 6 This is a schematic cross-sectional view showing a state where the ultrasonic coupling material film 1 is sandwiched between the skin 3 and the ultrasonic probe 4. Since the ultrasonic coupling material film 1 covers the irregularities of the skin 3, the ultrasonic wave 5 emitted from the ultrasonic probe 4 is transmitted to the skin.

[0147] on the other hand, Figure 7 It is also a schematic cross-sectional view of the state where the ultrasonic coupling material film 1 is clamped between the skin 3 and the ultrasonic probe 4. However, at this time, the ultrasonic coupling material film 1 does not cover the unevenness of the skin 3, so the ultrasonic wave 5 cannot be transmitted to the skin.

[0148] Figure 8 This is a photograph showing the state after one side of the release liner is peeled off, the ultrasonic coupling material film 1 is attached to the skin on the inner side of the forearm, and the other side of the release liner is peeled off.

[0149] Fig. 9 This is a photograph of a water-soluble ultrasonic coupling gel (water-soluble gel coupling material 6) dispensed from a tube onto the skin on the inner side of the forearm. After dispensing, the gel was spread with fingers to form an ultrasonic coupling material film.

[0150] Fig.10 This is a photograph of the handheld diagnostic ultrasound device 10 as viewed from the ultrasound probe 4 side.

[0151] Fig.11This is a photograph showing that the ultrasonic coupling material film 1 is attached to the ultrasonic probe of the ultrasonic diagnostic device 10 while the release liner 2 is peeled off. It can be seen that the ultrasonic coupling material film becomes an independent film.

[0152] Fig.12 This is a photograph showing a handheld ultrasonic diagnostic device placed on a coupling material film and measuring an ultrasonic image.

[0153] Fig.13 , 14 The ultrasonic image is obtained.

[0154] Ultrasonic diagnosis is performed by placing an ultrasonic probe in close contact with the skin, allowing the ultrasonic wave emitted from the probe surface to bounce off the body, and then detecting the information in the body with the probe receiver. When the ultrasonic wave is transmitted into the body and bounces off the target part, the following information can be obtained: Fig.13 On the other hand, when ultrasonic measurement is performed, if the surface to be measured has unevenness and an air layer is inserted, the ultrasonic wave emitted from the surface of the ultrasonic probe will be reflected by the air layer and cannot reach the body, resulting in Fig.14 Unclear ultrasound image shown.

[0155] That is, if Figure 6 Generally, the ultrasonic coupling material film 1 is held between the skin 3 and the ultrasonic probe 4. If the ultrasonic coupling material film 1 covers the unevenness of the skin 3, the ultrasonic wave 5 will be transmitted to the skin, so that Fig.13 Ultrasound image shown.

[0156] On the other hand, Figure 7 Generally, if the ultrasonic coupling material film 1 does not cover the unevenness of the skin 3, the ultrasonic wave 5 cannot be transmitted to the skin, so that Fig.14 Ultrasound image shown.

[0157] [Example]

[0158] Hereinafter, the present invention will be specifically described using Examples and Comparative Examples, but the present invention is not limited thereto. In addition, in the following, when the viscosity of the measured object exceeds 500,000 mPa·s, the viscosity (30% solution viscosity) when dissolved in toluene in a manner of 30% by mass is indicated. That is, when the viscosity is indicated by the 30% solution viscosity, it means that the viscosity of the measured object exceeds 500,000 mPa·s. The above absolute viscosity is a value measured at 25°C using a rotational viscometer.

[0159] [Examples 1 to 12, Comparative Examples 1 to 5]

[0160] The components used in Examples and Comparative Examples are as follows.

[0161] (Component A (Silicone Adhesive))

[0162] (component a)

[0163] The viscosity of the compound in a 30% by mass toluene solution is 27,000 mPa·s, the olefin content is 0.02 mol / 100 g, and the molecular chain ends are SiMe 2 The vinyl-containing polydimethylsiloxane terminated with a Vi group is siloxane compound 1.

[0164] The viscosity of the compound in a 30% by mass toluene solution is 27,000 mPa·s, the olefin content is 0.01 mol / 100 g, and the molecular chain ends are SiMe 2 The vinyl-containing polydimethylsiloxane terminated with a Vi group is siloxane compound 2.

[0165] In addition, the viscosity of Siloxane Compounds 1 and 2 at 25° C. was both 100,000 mPa·s or more.

[0166] (Component b)

[0167] Defined by Me 3 SiO 0.5 Unit and SiO 2 MQ resin polysiloxane (Me 3 SiO 0.5 Unit / SiO 2 A 60 mass % toluene solution of MQ resin 1 (unit = 0.8) is MQ resin 1.

[0168] Defined by Me 3 SiO 0.5 Unit and SiO 2 MQ resin polysiloxane (Me 3 SiO 0.5 Unit / SiO 2 A 60 mass % hexane solution of 1,2-dihydro-1,4 ...

[0169] Defined by Me 3 SiO 0.5 Unit and SiO 2 MQ resin polysiloxane (Me 3 SiO 0.5 Unit / SiO 2 The MQ resin 3 was a 60 mass % isoparaffin solvent ISOPAR (registered trademark) G solution containing 1,2-dimethyl-1,4-dihydro ...

[0170] (Component A (Silicone Adhesive))

[0171] 40 parts by weight of vinyl-containing polydimethylsiloxane having a viscosity of 42,000 mPa·s in a 30% by weight toluene solution, an alkenyl content of 0.02 mol / 100 g, and a molecular chain end-capped with OH, and Me 3 SiO 0.5 Unit and SiO 2 MQ resin polysiloxane (Me 3 SiO 0.5 Unit / SiO 2 A solution consisting of 100 parts by mass of a 60% toluene solution of 1,2-dimethylsiloxane (1,2-dimethylsiloxane) and 26.7 parts by mass of toluene was heated under reflux for 4 hours and then cooled. The siloxane compound 3 was defined as a solution in which polydimethylsiloxane was bonded to the MQ resin.

[0172] (Component B)

[0173] The non-crosslinked silicone oil used was KF-96 manufactured by Shin-Etsu Chemical Co., Ltd. as shown in Table 1. Its dynamic viscosity at 25° C. corresponds to the number before CS in the table. For example, the dynamic viscosity of “KF-96 1,000CS” is 1,000 mm 2 / s, the dynamic viscosity of "KF-96 100CS" is 100mm 2 / s. The dynamic viscosity is a value measured at 25°C using an Oswald viscometer.

[0174] (Component C)

[0175] As the methyl hydrogen silicone oil, KF-99 and KF-9901 manufactured by Shin-Etsu Chemical Co., Ltd. were used.

[0176] (additive)

[0177] Dry silica: AEROSIL RX200 (made by NIPPON AEROSIL, surface treated with trimethylsilyl)

[0178] (Organic Solvent)

[0179] ISOPAR TM G (ExxonMobil Corporation)

[0180] The coupling material solutions (ultrasonic coupling material compositions) described in Table 1 were mixed, and 1 part by mass of platinum catalyst PL-56 manufactured by Shin-Etsu Chemical Co., Ltd. was added to 100 parts by mass of the solutions, followed by further mixing.

[0181] [Table 1]

[0182]

[0183]

[0184] (Formation of coupling material film)

[0185] The ultrasonic coupling material solution was coated on a release liner of PET SEPARATOR SS1A (50 μm thickness) manufactured by NIPPA Co., Ltd. with a coating rod, air-dried for 10 minutes, and then baked in a hot air oven at 125° C. for 10 minutes for hardening to form a film as shown in FIG. Figure 1 After hardening, the coupling material film was covered with a release liner of PET SEPARATOR SS1A (50 μm thick) manufactured by NIPPA (stock company) to prepare a film as shown in FIG. Figure 2 A film of ultrasonic coupling material is shown sandwiched between a release liner.

[0186] (Comparative Example 5)

[0187] In Comparative Example 5, a known lubricant-like water-soluble gel coupling material 6 was used as the ultrasonic coupling material.

[0188] (Measurement of the thickness of the biocontact layer)

[0189] The thickness of the ultrasonic coupling material film prepared above was measured using a micrometer. The results are shown in Table 2.

[0190] Peel off the release liner on one side, and stick the ultrasonic coupling material film surface on the skin of the forearm. After sticking to the skin, peel off the release liner on the other side. Figure 8 As shown, a film of ultrasonic coupling material is formed on the skin.

[0191] The gel ultrasonic coupling material of Comparative Example 5 is a lubricant-like water-soluble gel coupling material 6 such as Fig. 9 The film thickness of the coupling material film cannot be measured.

[0192] (Measurement of Ultrasonic Information)

[0193] The handheld ultrasonic diagnostic device (ultrasound diagnostic meter) used for the measurement of ultrasonic information was SONON 500L manufactured by Healcerion. Fig.12 As shown, the probe surface of the ultrasonic diagnostic device was brought into contact with the ultrasonic coupling material film on the wrist, and ultrasonic diagnosis at a frequency of 8.5 MHz was performed.

[0194] The coupling material was attached to the wrist and the above-mentioned ultrasonic diagnosis was performed, and then the wrist was immersed in water for 1 minute, and then the wrist was dried and the ultrasonic diagnosis was performed. Thereafter, the coupling material film was peeled off from the skin, and the skin was visually observed for any residue.

[0195] (Water resistance evaluation)

[0196] When the ultrasonic diagnosis after water immersion is performed, the above Fig.13 If the image is clear, it is judged as good. Fig.14 If the image is not clear, it is judged as defective.

[0197] Table 2 shows the evaluation results of the ultrasonic coupling materials described in Table 1.

[0198] [Table 2]

[0199]

[0200] As shown in Table 2, when the ultrasonic coupling material films shown in Examples 1 to 12 in which silicone oil of component (B) is added to the silicone adhesive composed of components (a) and (b) is attached to the skin, a good ultrasonic image can be obtained, and the same image can be obtained even if the wrist is immersed in water, and there is no residue on the skin after the ultrasonic coupling material film is peeled off from the skin. On the other hand, in the case of the silicone adhesive of Comparative Example 1 to which component (B) is not added, the image measured by ultrasonic diagnosis is poor. In the case of the silicone gel containing MQ resin to which component (b) is not added as shown in Comparative Example 2, the ultrasonic image is good, but the residue of the silicone oil of component (B) added is produced after being peeled off from the skin. In Comparative Example 3 in which the dynamic viscosity of component (B) is too large, the ultrasonic image is poor, and on the contrary, in Comparative Example 4 in which the dynamic viscosity of component (B) is too small, the ultrasonic image is good, but the ultrasonic coupling material film is produced after being peeled off from the skin. The known water-soluble gel coupling material of Comparative Example 5 showed good ultrasonic images after the coupling material was applied, but when the wrist was immersed in water, the coupling material dissolved and the ultrasonic images were poor.

[0201] The ultrasonic coupling material of the present invention can embed the unevenness of the skin and provide a good ultrasonic image (that is, high ultrasonic transmission and sensitivity). Since it uses polysilicone as the main component, it has excellent biocompatibility and is lightweight. Moreover, the ultrasonic coupling material composition (solution) of the present invention can be used to manufacture an ultrasonic coupling material film at low cost by coating it on a support and hardening it as needed. The ultrasonic coupling material film does not contain water-soluble materials, so even if it is wetted or dried by water, the ultrasonic transmission will not be greatly reduced. Since it is a hardened material from (A) polysilicone adhesive, it is soft and has excellent elasticity. After peeling, no residue will remain on the skin, and it will not cause rough skin. In this way, the ultrasonic coupling material composition of the present invention has excellent characteristics.

[0202] This specification includes the following aspects.

[0203] [1]: An ultrasonic coupling material composition comprising (A) a polysilicone adhesive and (B) a silicone oil without crosslinking points, characterized in that:

[0204] The aforementioned polysiloxane adhesive (A) is a mixture or condensation reaction product of a diorganopolysiloxane (a) and a resin composition (b), wherein the viscosity of the diorganopolysiloxane (a) at 25° C. is 100,000 mPa·s or more, and the resin composition (b) contains a 1 3 SiO 1 / 2 and SiO 2 Unit resin and organic solvent; R 1 A hydrogen atom or a substituted or unsubstituted monovalent hydrocarbon group having 1 to 10 carbon atoms;

[0205] The aforementioned (B) silicone oil without crosslinking points has a dynamic viscosity of 10 to 100,000 mm at 25°C. 2 / s range.

[0206] [2]: The ultrasonic coupling material composition as described in [1], wherein the diorganopolysiloxane (a) is a diorganopolysiloxane (a1) having an alkenyl group.

[0207] [3]: The ultrasonic coupling material composition of [2] further contains an organic group hydrogen polysiloxane having a SiH group as component (C).

[0208] [4]: The ultrasonic coupling material composition of [3] further contains a platinum catalyst.

[0209] [5]: The ultrasonic coupling material composition according to [4], wherein the value obtained by dividing the number of moles of SiH groups in the component (C) by the number of moles of alkenyl groups in the component (A) is in the range of 0.5 to 20.

[0210] [6]: The ultrasonic coupling material composition as described in any one of [2] to [5], wherein the aforementioned component (B) is a linear or branched diorganopolysiloxane without alkenyl and SiH groups.

[0211] [7]: An ultrasonic coupling material composition as described in any one of [3] to [6], wherein the value of the mass of the aforementioned (B) component divided by the solid content of the aforementioned (a) component and the aforementioned (b) component and the total mass of the aforementioned (B) component and the aforementioned (C) component is in the range of 0.2 to 0.8.

[0212] [8]: An ultrasonic coupling material composition as described in any one of [3] to [7], further comprising 0.1 to 10 parts by mass of dry silica relative to 100 parts by mass of the solid content of the aforementioned component (a) and the aforementioned component (b) and the aforementioned component (B) and the aforementioned component (C) in total.

[0213] [9]: An ultrasonic coupling material film, which is composed of a cured product of the ultrasonic coupling material composition as described in any one of [1] to [8].

[0214]

[10] : The ultrasonic coupling material film as described in [9], wherein the film thickness of the ultrasonic coupling material film is in the range of 10 to 10000 μm.

[0215]

[11] : A single ultrasonic coupling material film, characterized in that it is a self-supporting film separated from the support body as the ultrasonic coupling material film of [9] or

[10] .

[0216]

[12] : A laminated structure comprising a support and an ultrasonic coupling material film such as [9] or

[10] directly in contact with the support.

[0217]

[13] : A method for forming a laminated structure, characterized in that: an ultrasonic coupling material composition as described in any one of [1] to [8] is coated on a peeling liner film, and heated and hardened to form an ultrasonic coupling material film, and then, the peeling liner film is peeled off from the ultrasonic coupling material film and the ultrasonic coupling material film is attached to another support body, and an ultrasonic probe is attached to the surface opposite to the surface contacting the other support body to form a laminated structure.

[0218]

[14] : A method for forming a laminated structure, characterized by: coating an ultrasonic coupling material composition as described in any one of [1] to [8] on a peeling liner film, heating and hardening it to form an ultrasonic coupling material film, then peeling off the peeling liner film from the ultrasonic coupling material film and attaching the ultrasonic coupling material film to an ultrasonic probe to form a laminated structure.

[0219]

[15] : A method for forming a laminated structure, characterized in that an ultrasonic coupling material composition as described in any one of [1] to [8] is coated on an ultrasonic probe, and heated and hardened to form an ultrasonic coupling material film to form a laminated structure.

[0220]

[16] : A method of examination, excluding methods for performing surgery, treatment or diagnosis on humans, characterized by: following the method for forming a laminated structure as described in any one of

[13] to

[15] , the ultrasonic probe is attached to the skin with the surface formed with the ultrasonic coupling material film to perform ultrasonic examination.

[0221] The present invention is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and those having substantially the same configuration as the technical concept described in the claims of the present invention and having the same functions and effects are all included in the technical scope of the present invention.

[0222] Description of Reference Numerals

[0223] 1: Coupling material (membrane)

[0224] 2: Support (release liner)

[0225] 3. Skin

[0226] 4: Ultrasonic probe

[0227] 5. Ultrasound

[0228] 6: Water-soluble gel coupling material

[0229] 10: Ultrasonic diagnostic instrument

Claims

1. An ultrasonic coupling material composition comprising (A) a polysilicone adhesive and (B) a silicone oil without crosslinking points, characterized in that: The polysilicone adhesive (A) is a mixture or condensation reaction product of a diorganopolysiloxane (a) and a resin composition (b), wherein the viscosity of the diorganopolysiloxane (a) at 25° C. is greater than 100,000 mPa·s, and the resin composition (b) contains a 1 3SiO 1 / 2 and SiO2 unit resin and organic solvent; R 1 A hydrogen atom or a substituted or unsubstituted monovalent hydrocarbon group having 1 to 10 carbon atoms; The (B) silicone oil without crosslinking point has a dynamic viscosity of 10 to 100,000 mm at 25°C. 2 / s range.

2. The ultrasonic coupling material composition according to claim 1, wherein: The diorganopolysiloxane (a) is a diorganopolysiloxane (a1) having an alkenyl group.

3. The ultrasonic coupling material composition according to claim 2 further comprises an organic group hydrogen polysiloxane having a SiH group as component (C).

4. The ultrasonic coupling material composition according to claim 3 further contains a platinum catalyst.

5. The ultrasonic coupling material composition according to claim 4, wherein: The value obtained by dividing the number of moles of SiH groups in the component (C) by the number of moles of alkenyl groups in the component (A) is in the range of 0.5 to 20.

6. The ultrasonic coupling material composition according to claim 2, wherein: The component (B) is a linear or branched diorganopolysiloxane having no alkenyl group or SiH group.

7. The ultrasonic coupling material composition according to claim 3, wherein: The value obtained by dividing the mass of the component (B) by the solid content of the component (a) and the component (b) and the total mass of the component (B) and the component (C) is in the range of 0.2 to 0.

8.

8. The ultrasonic coupling material composition according to claim 3, wherein: The present invention further contains 0.1 to 10 parts by mass of dry silica based on 100 parts by mass of the total solid content of the components (a) and (b) and the components (B) and (C).

9. An ultrasonic coupling material film, comprising a cured product of the ultrasonic coupling material composition according to any one of claims 1 to 8.

10. The ultrasonic coupling material film according to claim 9, wherein: The film thickness of the ultrasonic coupling material film is in the range of 10 to 10000 μm.

11. A single ultrasonic coupling material film, characterized by: The ultrasonic coupling material film according to claim 9 is a self-supporting film separated from the support.

12. A laminated structure, comprising a support and the ultrasonic coupling material film according to claim 9 directly contacting the support.

13. A method for forming a laminated structure, characterized in that: an ultrasonic coupling material composition according to any one of claims 1 to 8 is coated on a peeling liner film, and heated and hardened to form an ultrasonic coupling material film, and then, the peeling liner film is peeled off from the ultrasonic coupling material film and the ultrasonic coupling material film is attached to another support body, and an ultrasonic probe is attached to the surface opposite to the surface contacting the other support body to form a laminated structure.

14. A method for forming a laminated structure, characterized in that: an ultrasonic coupling material composition according to any one of claims 1 to 8 is coated on a peeling liner film, heated and hardened to form an ultrasonic coupling material film, and then, the peeling liner film is peeled off from the ultrasonic coupling material film and the ultrasonic coupling material film is attached to an ultrasonic probe to form a laminated structure.

15. A method for forming a laminated structure, characterized by: The ultrasonic coupling material composition according to any one of claims 1 to 8 is coated on an ultrasonic probe, and is heated and hardened to form an ultrasonic coupling material film to produce a laminated structure.

16. A method of examination, excluding surgery, treatment or diagnosis on human beings, characterized by: Following the method for forming a laminated structure according to claim 14, the ultrasonic probe is attached to the skin with the surface on which the ultrasonic coupling material film is formed, and ultrasonic examination is performed.

17. A method of examination, excluding surgery, treatment or diagnosis on human beings, characterized by: Following the method for forming a laminated structure according to claim 15, the ultrasonic probe is attached to the skin with the surface on which the ultrasonic coupling material film is formed, and ultrasonic examination is performed.

Citation Information

Patent Citations

  • Ultrasonic coupling material

    JP1988019135A

  • Ultrasound interfacing device for tissue imaging

    JP2005532871A

  • Gentle-to-skin adhesive

    JP2015028178A

  • Silicone adhesive composition, manufacturing method therefore and adhesive film

    JP2015193803A

  • Silicone release agent composition, release sheet and release film

    JP2020100763A